2017
DOI: 10.1186/s12877-017-0461-0
|View full text |Cite
|
Sign up to set email alerts
|

Is independence of older adults safe considering the risk of falls?

Abstract: BackgroundFalls affect approx. 30% of elderly population per year. They cause major injuries and reduce independence of the older adults’ functioning. The main objective of the study was to evaluate the degree of independence and find the fall risk factors in the study group.MethodsThe study included 506 – older adults. The study group included patients from GP clinics and members of two senior centers. The study duration was 12 months. Our study tools included EASY- Care Standard 2010 questionnaire, Abbreviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
0
10
0
9
Order By: Relevance
“…Pain, insomnia, and depressive symptoms are common health problems in older adults and may contribute to falls [ 6 9 ]. More than 50% of US older adults report pain and the majority of them have multiple pain sites [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pain, insomnia, and depressive symptoms are common health problems in older adults and may contribute to falls [ 6 9 ]. More than 50% of US older adults report pain and the majority of them have multiple pain sites [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 375 individuals were considered not to tend to fall, and it was found that 79 of those had previously fallen. In that study, therefore, 177 of the 506 participants had previously fallen, which is approximately 34% (10). In our study, however, only 21 of the participants (17.6%) had previously fallen; therefore, having a history of falls was not a serious risk factor in our experience.…”
Section: Discussionmentioning
confidence: 45%
“…É vista como um item primordial na atenção à saúde do idoso, uma vez que está expande o campo de visão acerca do processo de avaliação saúde doença. A mesma pode ser avaliada considerando dois aspectos: Atividades Instrumentais de Vida Diária (AIVD) e Atividades Básicas de Vida Diária (ABVD) (TALARSKA D, et al, 2017;CARVALHO TC, et al, 2018). As AIVD's correspondem às ações mais complexas que referem-se a competência de ter independência na sociedade como: fazer compras, usar o telefone, dirigir, usar transporte coletivo, manusear o próprio dinheiro ou administrar seus remédios.…”
Section: Introductionunclassified